2001
DOI: 10.2343/geochemj.35.29
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of the Re-Os chronometer of molybdenites from the late-Caledonian Galway Granite, Ireland, by hydrothermal fluid circulation.

Abstract: Re-Os ages were determined for molybdenites from the late-Caledonian Galway Granite in the west of Ireland. Molybdenites from three localities within the batholith, Mace Head, Murvey, and Travore, yield respective Re-Os ages of 425.2 ± 3.1 Ma, 383.2 ± 8.1 and 426.1 ± 5.5 Ma, and 338.9 ± 5.6 and 464 ± 28 Ma. The molybdenites from the three localities are believed to be contemporaneous. However, the Re-Os ages obtained for each locality are not only in disagreement with the ages of the samples from the other loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
4
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 27 publications
1
31
4
1
Order By: Relevance
“…These dates are in agreement with those reported by Stein et al (1997) (221.5 ± 0.3 Ma) and Markey et al (1998) (221.3 ± 0.2 Ma), which were obtained through the different techniques of alkaline fusion and NTIMS techniques. The HLP-5 Re-Os age reported by Suzuki et al (2001) is also in agreement with an average Re-Os age of HLP-5 of 220.5 ± 0.5 Ma reported by Selby et al (2003), obtained by Carius tube methods and NTIMS isotopic analysis. It is important to note that the HLP-5 "control" sample is a 2 kg powder concentrate (~44 µm) obtained from separating ~0.13 to 0.2 mm molybdenite (Du Andao, pers.…”
Section: Critical Commentsupporting
confidence: 78%
See 4 more Smart Citations
“…These dates are in agreement with those reported by Stein et al (1997) (221.5 ± 0.3 Ma) and Markey et al (1998) (221.3 ± 0.2 Ma), which were obtained through the different techniques of alkaline fusion and NTIMS techniques. The HLP-5 Re-Os age reported by Suzuki et al (2001) is also in agreement with an average Re-Os age of HLP-5 of 220.5 ± 0.5 Ma reported by Selby et al (2003), obtained by Carius tube methods and NTIMS isotopic analysis. It is important to note that the HLP-5 "control" sample is a 2 kg powder concentrate (~44 µm) obtained from separating ~0.13 to 0.2 mm molybdenite (Du Andao, pers.…”
Section: Critical Commentsupporting
confidence: 78%
“…molybdenite from this study contrast with those reported by Suzuki et al (2001) (Table 1). Firstly, our Re and 187 Os contents are highly reproducible for replicate analyses of the same sample.…”
Section: Critical Commentcontrasting
confidence: 56%
See 3 more Smart Citations